2018
DOI: 10.1016/j.jtcvs.2017.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transdiaphragmatic chest surgery: Early experience

Abstract: Early experience suggests that LTD chest surgery is feasible and safe on short- to midterm follow-up. The specific role of LTD chest surgery will require definition of patient selection criteria, further experience to reduce operative time, long-term follow-up, and prospective comparison with conventional VATS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Transdiaphragmatic approach which was described by Andrade et al involves introduction of 4 laparoscopic ports including 2 intrathoracic ports inserted through diaphragmatic openings (33). An intrathoracic resection was performed in a standard VATS technique, a specimen was retrieved through the abdomen and the diaphragmatic openings which were finally closed.…”
Section: Transdiaphragmatic Approachmentioning
confidence: 99%
“…Transdiaphragmatic approach which was described by Andrade et al involves introduction of 4 laparoscopic ports including 2 intrathoracic ports inserted through diaphragmatic openings (33). An intrathoracic resection was performed in a standard VATS technique, a specimen was retrieved through the abdomen and the diaphragmatic openings which were finally closed.…”
Section: Transdiaphragmatic Approachmentioning
confidence: 99%
“…Twenty-eight patients who underwent laparoscopic transdiaphragmatic VATS procedures using two-port entry sites to access the thoracic cavity with curative intent due to various etiologies, were reported by Andrade et al Authors did not report an exclusion criteria but recommended avoiding such procedure in patients with a body mass index (BMI) ≥ 35 kg/m2. In addition, they recommended avoiding the left transdiaphragmatic approach in relatively young patients or those who practice heavy lifting due to increased possibility of herniation [15].…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported chest tube insertion before wound closure without emphasizing how long it remained inside the chest cavity and when it was removed. They also reported pulmonary complications, such as pneumonia, air-leak, atelectasis, and pleural effusion without a clear postoperative timeline [13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…There are some reported cases of lower posterior mediastinal tumor resection using a transdiaphragmatic approach by laparoscopic surgery in the literature. [ 10 – 14 ] They were all used the transperitoneal approach. However, we have reported the first case of a lower posterior mediastinal benign schwannoma that was successfully retroperitoneoscopic resected using a transdiaphragmatic approach.…”
Section: Discussionmentioning
confidence: 99%